ATTENUATION ANALYSIS OF VSP DATA - Suprajitno Munadi (Testing Center for Oil and Gas LEMIGAS, 1987)
Attenuation is usually defined to include all types of frequency selective process wich contribute to the am- plitude decay of propagating waves. It depends on porosity of rock, grain size, over pressure zones and fluid saturation. Attenuation can at least double the information obtained from velocities alone. The measurement of attenuation from a Vertical Seismic Profiles (VSP) has been carried out using two dif- ferent methods ie. the Spectral Magnitude Decay Method and the Pulse Broadening Method. The Spectral Magni- tude Decay Method is executed in the frequency domaiün, while the Pulse Broadening Method is entirely executed in the time domain. Both methods have been tested using two shallow, high resolution VSP data. The deduced quality factor Q. obtained from the Spectral Magnitude Decay Method is slightly lower than those obtained from the Pulse Broadening Method. Thèse discTepancies can be attributed to reflection/transmission loses at layer boundaries which are lumped together with absorption in the frequency domain estimates.